2022
DOI: 10.1039/d2tc03144b
|View full text |Cite
|
Sign up to set email alerts
|

Onion-like Fe3O4/MgO/CoFe2O4 magnetic nanoparticles: new ways to control magnetic coupling between soft and hard magnetic phases

Abstract: The control of the magnetization inversion dynamics is one of the main challenges driving the design of new nanostructured magnetic materials for magnetoelectronic applications. Nanoparticles with onion-like architecture offer a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Ong et al investigated a monodisperse Fe/Fe3O4 core/shell as well as Fe3O4 hollow-shell nanoparticles and observed a much larger EB in the first, but sharp demagnetization jumps at low fields due to the sudden switching of shell magnetic moments for both nanoparticles [142]. Nunez et al recently reported a large coercivity of nearly 6 kOe at 5 K and an EB for Fe3O4/MgO/CoFe2O4 core-shell-shell nanoparticles, which they attributed to the freezing of the surface spins, pinning the magnetic moments of the CoFe2O4 shell [143]. Combining Fe3O4 with manganese oxide as the core or shell, Estrader et al observed a horizontal EB shift in three different nanostructures after cooling in small fields, while a large cooling field resulted in a sign change in the EB for both structures with iron oxide cores and reduced the EB to nearly zero for the nanoparticles with manganese oxide cores [144].…”
Section: Other Iron-oxide-based Exchange-biased Nanostructuresmentioning
confidence: 99%
“…Ong et al investigated a monodisperse Fe/Fe3O4 core/shell as well as Fe3O4 hollow-shell nanoparticles and observed a much larger EB in the first, but sharp demagnetization jumps at low fields due to the sudden switching of shell magnetic moments for both nanoparticles [142]. Nunez et al recently reported a large coercivity of nearly 6 kOe at 5 K and an EB for Fe3O4/MgO/CoFe2O4 core-shell-shell nanoparticles, which they attributed to the freezing of the surface spins, pinning the magnetic moments of the CoFe2O4 shell [143]. Combining Fe3O4 with manganese oxide as the core or shell, Estrader et al observed a horizontal EB shift in three different nanostructures after cooling in small fields, while a large cooling field resulted in a sign change in the EB for both structures with iron oxide cores and reduced the EB to nearly zero for the nanoparticles with manganese oxide cores [144].…”
Section: Other Iron-oxide-based Exchange-biased Nanostructuresmentioning
confidence: 99%
“…Another novel material synthesis method for 0-3 nanocomposite fabrication has recently been accomplished by containing both the hard and soft magnetic interaction within a single nanoparticle, using "onion-like" nanoparticles of Fe 3 O 4 /MgO/CoFe 2 O 4 . 62 Additionally, Fe 3 C/CoFe 2 O 4 nanocomposites have been synthesized via a chemical co-precipitation method wherein the two phases share interfaces within the material. 63 Incorporation of particles such as these into a nanoparticle film would then allow for the deployment of these materials as power components with improved magnetic performance, potentially only with the need for the infiltrated matrix to stabilize the film for device use.…”
Section: Future Directionsmentioning
confidence: 99%
“…Another novel material synthesis method for 0‐3 nanocomposite fabrication has recently been accomplished by containing both the hard and soft magnetic interaction within a single nanoparticle, using “onion‐like” nanoparticles of Fe 3 O 4 /MgO/CoFe 2 O 4 62 . Additionally, Fe 3 C/CoFe 2 O 4 nanocomposites have been synthesized via a chemical co‐precipitation method wherein the two phases share interfaces within the material 63 .…”
Section: Future Directionsmentioning
confidence: 99%
“…Other researchers reported the fabrication of onion-like Fe 3 O 4 /MgO/CoFe 2 O 4 core–shell–shell nanostructures with the magnetite mean core size of 22 ± 4 nm coated with an inner shell of magnesium oxide and an outer core of cobalt ferrite of thicknesses ≈1 and ≈2.5 nm, respectively. The magnetization measurements at the temperature T = 5 K revealed enhancement of the coercivity field, from H C ≈ 48.3 kA/m for the Fe 3 O 4 /MgO to H C ≈ 468.7 Oe for the Fe 3 O 4 /MgO/CoFe 2 O 4 nanoparticles, attributed to the magnetic coupling between both ferrimagnetic phases . To the best of our knowledge, no investigations about SAR assessment of this kind of nanoparticles can be found in the literature, thus representing TMNPs as a viable alternative to conventional hyperthermia where high doses of therapeutic agents are required. …”
Section: Introductionmentioning
confidence: 98%
“…The magnetization measurements at the temperature T = 5 K revealed enhancement of the coercivity field, from H C ≈ 48.3 kA/m for the Fe 3 O 4 /MgO to H C ≈ 468.7 Oe for the Fe 3 O 4 /MgO/CoFe 2 O 4 nanoparticles, attributed to the magnetic coupling between both ferrimagnetic phases. 26 To the best of our knowledge, no investigations about SAR assessment of this kind of nanoparticles can be found in the literature, thus representing TMNPs as a viable alternative to conventional hyperthermia where high doses of therapeutic agents are required. 27−29 Current research shows that the therapeutic efficacy of MFH is limited by poor stabilization of MNPs in aqueous environments and their bioavailability or by the lack of targeting specificity in tumors.…”
Section: Introductionmentioning
confidence: 99%